Information checking as a form of character management in education - Zulfah Zulfah; Rizka Amalia Shofa (Journal of Social Studies (JSS), 2020)
Research with information checking as a form of character management in education aims to determine the level of curiosity and responsibility of society, in this case, young people to report, to see how they manage the information obtained and disseminated. This research was conducted by survey method. The sampling technique using proportionate stratified random sampling to get a sample from the population in Vocational Health of Sadewa Yogyakarta. Instruments data acquisition using a questionnaire that contained 15 questions covering questions in the curiosity and responsibility for the information obtained. Based on the data obtained, it was found that there is a nursing class score of interest is 134, and commitment is 98. While the pharmaceutical grade score of curiosity is 148, and accountability is 78. The item of interest looked more significant than the things responsible for the information. Based on the calculation to be obtained percentage nursing class of 65.5% and pharmaceutical grade amounted to 67.25%. It is certainly still far from the ideals percentage of 100%. So it needs more attention to the cultivation of character the young generation in the era of freedom of information.